Ultrasonic quantification, value of color and contribution of transcranial Doppler sonography in carotid artery surgery - Berni, A; Cavaiola, S; Mele, R; Tombesi, T; Custureri, F; D'Andrea, V; Marchesi, M; Tromba, L (Minerva cardioangiologica, 1996)
The authors briefly report their experience regarding the opportunities offered by the use of current ultrasound methods in carotid surgery. They describe: a system for the quantification of athcromasic plaque used to monitor non-operated patients over time; ultrasound methods used to analyse the carotid wall to establish whether it can be utilised as an index of vascular aggression in hypertension, diabetes and atherosclerosis; the use of transcranial Doppler; criteria for the definition of high risk plaque; the applications of eco-color Doppler. The paper also illustrates a new pathology identified by the authors, defined as primary intimal fibrous hyperplasia, and the evolution of the carotid wall after endarterectomy. The structural characteristics of primary hyperplasia can only be shown using ultrasound given that arteriography cannot distinguish it from atheromatic stenosis. After endarterectomy the carotid wall is subject to hematic and hemodynamic stimuli which determine the type of evolution of the wall itself. The authors therefore examine the myointimal reaction, myointimal hyperplasia, early restenosis and late restenosis as different facets of the same phenomenon.